Molecular Targeting of HuR Oncoprotein Suppresses MITF and Induces Apoptosis in Melanoma Cells - Ahmed, Rebaz (Cancers (Basel), 2021)
SIMPLE SUMMARY: The human antigen R (HuR) protein regulates the expression of hundreds of proteins in a cell that support tumor growth, drug resistance, and metastases. HuR is overexpressed in several human cancers, including melanoma, and is a molecular target for cancer therapy. Our study objective, therefore, was to develop HuR-targeted therapy for melanoma. We identified that HuR regulates the microphthalmia-associated transcription factor (MITF) that has been implicated in both intrinsic and acquired drug resistance in melanoma and is a putative therapeutic target in melanoma. Using a gene therapeutic approach, we demonstrated silencing of HuR reduced MITF protein expression and inhibited the growth of melanoma cells but not normal melanocytes. However, combining HuR-targeted therapy with a small molecule MEK inhibitor suppressed MITF and produced a synergistic antitumor activity against melanoma cells. Our study results demonstrate that HuR is a promising target for melanoma treatment and offers new combinatorial treatment strategies for overriding MITF-mediated drug resistance. ABSTRACT: Background: Treatment of metastatic melanoma possesses challenges due to drug resistance and metastases. Recent advances in targeted therapy and immunotherapy have shown clinical benefits in melanoma patients with increased survival. However, a subset of patients who initially respond to targeted therapy relapse and succumb to the disease. Therefore, efforts to identify new therapeutic targets are underway. Due to its role in stabilizing several oncoproteins’ mRNA, the human antigen R (HuR) has been shown as a promising molecular target for cancer therapy. However, little is known about its potential role in melanoma treatment. Methods: In this study, we tested the impact of siRNA-mediated gene silencing of HuR in human melanoma (MeWo, A375) and normal melanocyte cells in vitro. Cells were treated with HuR siRNA encapsulated in a lipid nanoparticle (NP) either alone or in combination with MEK inhibitor (U0126) and subjected to cell viability, cell-cycle, apoptosis, Western blotting, and cell migration and invasion assays. Cells that were untreated or treated with control siRNA-NP (C-NP) were included as controls. Results: HuR-NP treatment significantly reduced the expression of HuR and HuR-regulated oncoproteins, induced G1 cell cycle arrest, activated apoptosis signaling cascade, and mitigated melanoma cells’ aggressiveness while sparing normal melanocytes. Furthermore, we demonstrated that HuR-NP treatment significantly reduced the expression of the microphthalmia-associated transcription factor (MITF) in both MeWo and MITF-overexpressing MeWo cells (p < 0.05). Finally, combining HuR-NP with U0126 resulted in synergistic antitumor activity against MeWo cells (p < 0.01). Conclusion: HuR-NP exhibited antitumor activity in melanoma cells independent of their oncogenic B-RAF mutational status. Additionally, combinatorial therapy incorporating MEK inhibitor holds promise in overriding MITF-mediated drug resistance in melanoma.